The wretched of the earth - Fanon, Frantz, 1925-1961 (Grove Press, 2021)
"First published in 1961, and reissued in this sixtieth anniversary edition with a powerful new introduction by Cornel West, Frantz Fanon's The Wretched of the Earth is a masterful and timeless interrogation of race, colonialism, psychological trauma, and revolutionary struggle, and a continuing influence on movements from Black Lives Matter to decolonization. A landmark text for revolutionaries and activists, The Wretched of the Earth is an eternal touchstone for civil rights, anti-colonialism, psychiatric studies, and Black consciousness movements around the world. Alongside Cornel West's introduction, the book features critical essays by Jean-Paul Sartre and Homi K. Bhabha. This sixtieth anniversary edition of Fanon's most famous text stands proudly alongside such pillars of anti-colonialism and anti-racism as Edward Said's Orientalism and The Autobiography of Malcolm X"--